Academic performance and use of social networks in undergraduate engineering students at a peruvian university - Abregú Jaucha, Washington Neuman (2023)
The general objective of the research was to determine the relationship between academic performance and the use of social networks in undergraduate students of the Faculty of Engineering at Universidad Peruana Los Andes. The research was of an applied type, level and descriptive method, respectively, and with a correlational descriptive design. The population was 1316 students from the Faculty of Engineering and 298 students were taken as an intentional sample made up of the five professional schools of the first cycles. The theory to understand social networks is from Adam Alter, on behavioral addictions. The instruments were the academic performance data record form (RDRA) and the frequency of use in social networks data record form (RDFURS). For data processing, descriptive and inferential statistics were used, where Pearson's "r" test and the chi-square test were used. As a result, 49,3% of students from the first to the fifth cycle have low academic performance; and of an intermediate use in social networks, with 57%. These results determined that X2=11,113; therefore, the statistical decision was made to accept the alternative hypothesis.